(untitled) (Tokyo, Japan, 1976)
This book consists of the following many parts: with respect to intercultural communication, between the rich and the poor, one self, many cultures, in the wake of technology, colloquy.
Keywords: Communication,Intercultural communication; Social aspects,Congresses,Congresses